Analisis Kontrastif Kosakata Bahasa Jawa Serang (Bebasan) dan Bahasa Betawi dalam Film Si Doel Versi Youtube Season 1 dan 2 - Ananda Cahya Camila; Siti Nurjanah; Odien Rosidin (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study aims to recognize and compare the vocabulary used in Serang Javanese and Betawi language in the YouTube Version of Si Doel Movie in Season 1 and 2. The approach used is descriptive qualitative by using contrastive analysis technique. Data were obtained by observing the dialog in the movie, as well as conducting interviews with native speakers of both languages. The findings of this study show that there are vocabularies that have the same form and meaning (10 vocabularies), similar forms but the same meaning (9 vocabularies), and different forms but the same meaning (45 vocabularies). This difference shows the characteristics of each regional language, even though they are geographically located in close proximity. This study emphasizes the importance of maintaining local languages and understanding vocabulary variation in inter-dialect communication.